Penerimaan Masyarakat Indonesia dan Masyarakat Jepang terhadap Iklan Produk Jepang - Shinji, Muhammad Rifan; Pryanka, Petra Theda; Fayumi, Ghefira Akyla (East Asian Review, 2025)
This research aims to compare Japanese product advertisements shown in Japan and Indonesia based on the reception and perspectives of the respective societies, which play a role in the acceptance of these advertisements. The data was obtained from the opinions of Indonesian and Japanese people through previously distributed questionnaires. The analysis uses qualitative methods based on Stuart Hall’s reception theory and Hurlock’s social acceptance theory. The reception theory is used to identify perspectives and meanings acquired by viewers from both Indonesian and Japanese people. The social acceptance theory is employed to analyze the effectiveness of advertisements in their approach to audiences, considering the cultural context within them. The results indicate differences in Japanese product advertisements between Indonesian and Japanese. The differences lie in visualization, storyline, and celebrity endorsers. Furthermore, it was found that respondents from both countries had mutual interest in the advertisements.